Suicide attempts and behavioral correlates among a nationally representative sample of school-attending adolescents in the Republic of Malawi - Masood A. Shaikh; Jennifer Lloyd; Emmanuel Acquah; Karen L. Celedonia; Michael L. Wilson (BioMed Central Ltd., 2022)
Background: Suicide is among the top causes of adolescent mortality worldwide. While correlates of suicidal
behavior are better understood and delineated in upper-income countries, epidemiologic knowledge of suicidal behavior in low-income countries remains scant, particularly in the African continent. The present study sought to add to the epidemiologic literature on suicidal behavior in Africa by examining the behavioral correlates of suicide attempts among Malawi adolescents.
Methods: A cross-sectional study using a nationally-representative sample extracted from publically-available data was conducted. Bivariate and multivariate analyses were performed to discern associations between suicide attempts and a host of behavioral variables. 2225 records were included in the study.
Results: At the multivariate level, suicide attempters had significantly higher odds of being anxious, being
physically bullied, having sustained a serious injury and having a greater number of lifetime sexual partners.
Alcohol use (at an early age and within the past 30 days) was also associated with suicide attempts.
Conclusions: These findings have the potential to guide public health interventions geared toward suicide
prevention in Africa and other, similar regions, as well as provide the impetus for future epidemiologic studies on suicidal behavior in low-income countries.